The Brexit as a Forerunner: Monetary Policy, Economic Order and Divergence Forces in the European Union - Sebastian Müller; Gunther Schnabl (Center for Economic Studies and ifo Institute (CESifo), 2018)
We analyze the effects of the increasingly expansionary monetary policies on the economic order and on the European integration process. We argue that the market orders shaped in postwar Germany and in Margret Thatcher's United Kingdom have long served as cornerstones for growth, prosperity and social cohesion in Europe. It is shown that the monetary policies of the European Central Bank and the Bank of England have undermined these orders, thereby eroding productivity gains and growth. Combined with negative distribution effects, ultra-loose monetary policies constitute the breeding ground for divergence forces in the European Union as heralded by the Brexit.
Keywords: B25; E58; E65; 330; European integration; economic order; Walter Eucken; Friedrich August von Hayek; Margret Thatcher; inequality; monetary policy; political polarization; divergence; Brexit